Cave Pygmarrhopalites Vargovitsh, 2009 (Collembola, Symphypleona, Arrhopalitidae) in United States - Zeppelini, Douglas; Taylor, Steven J.; Slay, Michael E. (Zootaxa, 2009)
Six new species of Collembola of the family Arrhopalitidae are described from the United States (Pygmarrhopalites leonardwoodensis sp. nov., P. plethorasari sp. nov., P. youngsteadtii sp. nov., P. buffaloensis sp. nov., P. shoshoneiensis sp. nov., and P. ashcraftensis sp. nov.) from caves in Missouri (2 spp.), Arkansas (2 spp.), Nevada, and Indiana, respectively. These new taxa, which display varying degrees of troglomorphy, are compared with previously known species and bring the total described species in North America to 41.